Das Porträt von Oskar in der Küche von Georgina Beier in Sydney (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Artists; Portraits; Interior decoration; Photographs; Sydney